2011
DOI: 10.1371/journal.pone.0025840
|View full text |Cite
|
Sign up to set email alerts
|

All Eggs Are Not Equal: The Maternal Environment Affects Progeny Reproduction and Developmental Fate in Caenorhabditis elegans

Abstract: BackgroundMaternal effects on progeny traits are common and these can profoundly alter progeny life history. Maternal effects can be adaptive, representing attempts to appropriately match offspring phenotype to the expected environment and are often mediated via trade-offs between progeny number and quality. Here we have investigated the effect of maternal food availability on progeny life history in the free-living nematode Caenorhabditis elegans.Methodology/Principal FindingsThe maternal environment affects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 30 publications
2
30
0
Order By: Relevance
“…It is, of course, possible that parallel maternal and offspring-specific developmental and physiological mechanisms determined adaptation, besides glycogen provisioning and possibly consumption, which could have increased embryo survival under anoxia [50,74,79,80]. We can conclude, however, that oocyte-size-related traits were not involved, as might have been expected from classical life-history theory predicting a fitness tradeoff between offspring size and number under resourcelimited situations (S7 Fig; but see [81,82]). …”
Section: Discussionmentioning
confidence: 58%
“…It is, of course, possible that parallel maternal and offspring-specific developmental and physiological mechanisms determined adaptation, besides glycogen provisioning and possibly consumption, which could have increased embryo survival under anoxia [50,74,79,80]. We can conclude, however, that oocyte-size-related traits were not involved, as might have been expected from classical life-history theory predicting a fitness tradeoff between offspring size and number under resourcelimited situations (S7 Fig; but see [81,82]). …”
Section: Discussionmentioning
confidence: 58%
“…This effect of social behaviour on dauer larvae formation is a clear example of an indirect effect on dauer larvae development, particularly given that it has previously been shown that there is no effect of bordering on dauer larvae development in standard dauer assays (Viney et al, 2003). As lower numbers of dauer larvae are observed in the npr-1 mutants, the opposite result to what one might predict if clumping behaviour produces high local pheromone concentrations and low local food levels, the reduction of dauer larvae development may be similar to the effects on dauer larvae development seen as a consequence of reduced maternal food availability (Harvey and Orbidans, 2011), that is, a harsher maternal environment resulting in the production of progeny that are less likely to develop as dauer larvae. The reduced numbers of dauer larvae formed in the npr-1 mutants also suggests that there is significant genetic variation which would act to increase dauer larvae development in many wild isolates (Figure 1), as the majority of these lines display the clumping phenotype.…”
Section: Discussionmentioning
confidence: 88%
“…QTLs defined only by sequential IL mapping are shown in bold. Butcher et al, 2007;Pungaliya et al, 2009;Park et al, 2012), on food availability and temperature (Golden and Riddle, 1984) and potentially on an assessment of individual quality (Harvey and Orbidans, 2011). Within growing populations, variation between genotypes in the number of dauer larvae could therefore be a consequence of variation in traits that affect the likelihood of dauer larvae development, the perception of the environment, or the way in which the population grows.…”
Section: Discussionmentioning
confidence: 99%
“…Early experience also modulates adult behaviors in the nematode Caenorhabditis elegans, and recent studies suggest that a subset of these effects can be transmitted to descendants (Rose et al 2005;Ebrahimi and Rankin 2007;Hall et al 2010;Remy 2010;Harvey and Orbidans 2011). Environmental cues experienced during early larval stages regulate a particularly critical developmental decision in C. elegans.…”
Section: Introductionmentioning
confidence: 99%